Signal Amplification Strategy for Highly Sensitive Detecting Brombuterol with Electrochemiluminescent Immunoassay by Using CdSe QDs as Label and Gold Nanoparticle as Substrate. Issue 8 (25th July 2016) - Dong, Tiantian; Yangxiao, Kete; Zhao, Kang; Deng, Anping; Li, Jianguo
Abstract: A signal amplification strategy for electrochemiluminescence (ECL) immunosensor was designed based on gold nanoparticles (AuNPs) and L‐cysteine capped CdSe QDs for highly sensitive detection of brombuterol (Brom) in the presence of K2 S2 O8 as the co‐reactant. Therein, AuNPs as the substrate can simplify the experiment process, accelerate the electron transfer rate, and enhance the ECL signal. In the presence of Brom standard solution, coating antigen immobilized on the electrode surface via AuNPs would compete with Brom for the limited binding sites of the CdSe QDs labeled Brom antibody. There was a linear relationship between the logarithm of the Brom concentration and ECL signal. Under the optimal conditions, immunosensor had a good linear range in 0.01–1000 ng mL −1 and a lower detection limit at 0.003 ng mL −1 . The specificity and stability of the immuneosensor was also studied, it has been used for the determination of Brom in real samples with satisfactory results. The proposed immunosensor will extend the application of QDs in ECL immunoassays and open a new road for the detection of other small molecules in the future. Abstract :